Application of indirect plasma-processed air on microbial inactivation and quality of yellow peaches during storage. (July 2022) - Wu, Qingyan; Shen, Chaoyi; Li, Jiangkuo; Wu, Di; Chen, Kunsong
Abstract: In this study, the effects of indirect plasma-processed air (PPA) treatments for 30, 120 and 240 s on Monilinia fructicola, indigenous microbes and quality of 'Jinxiu' yellow peaches were assessed. The results indicated that PPA-240 treatment had the best decontamination effect. For the disease incidence caused by inoculated M. fructicola, PPA-240 treatment reduced the incidence by 30.00%, 30.00%, and 36.67% on day 5, 6 and 7 of storage, respectively. PPA-240 treatment also reduced indigenous bacterial and fungal contamination by 1.67 log10 CFU/g and 0.98 log10 CFU/g on day 0, and consistently reduced the total number of indigenous microbes by more than 1.4 log10 CFU/g during storage. Metabolomics analysis showed that PPA-240 treatment induced the accumulation of gallocatechin in the pericarp and DHHP results indicated that the antioxidant activity of the pericarp was also increased. In addition, the indirect PPA treatment did not negatively affect total soluble solids, firmness, and color of yellow peaches. Graphical abstract: Unlabelled Image Highlights: Indirect PPA reduced 36.67% disease incidence of inoculated Monilinia fructicola. PPA reduced total indigenous microbes by over 1.4 log10 CFU/g during storage. PPA did not negatively affect the quality of yellow peach during 16 days of storage. PPA induced the accumulation of gallocatechin in the pericarp of yellow peach.